FAKTOR-FAKTOR RISIKO YANG MEMPENGARUHI STUNTING PADA BALITA : LITERATUR RIVIEW - Anisa Putri; Lilis Lismayanti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Stunting is a chronic nutritional problem that affects children’s growth and development, intelligence, and long-term productivity. This study aims to analyze the factors associated with stunting incidence based on a literature review of several relevant research articles. The research method used a literature review design with article sources from Google Scholar, PubMed, and Portal Garuda, spanning publication years from 2019 to 2024. After a process of identification, screening, and full-text eligibility assessment, 6 articles were obtained for analysis. The results of the study indicate that stunting is influenced by various factors, including low birth weight (LBW), which is proven to be a significant risk factor, inadequate nutritional intake and improper complementary feeding (MP-ASI) practices, low maternal education and knowledge, and parental economic status along with poor sanitation and environmental conditions. Furthermore, recurrent infections such as rotavirus-induced diarrhea also contribute to impaired nutrient absorption in children, increasing the risk of stunting. Thus, stunting is a multifactorial problem that requires integrated interventions through improved maternal and child health, sanitation improvement, nutritional education, and infection prevention as a comprehensive effort to reduce its prevalence.